Optimizing dual-band antenna efficiency: Ridge width parametric study of quad ridge horn antennas - Othman, Mohd Azlishah; Adnan, Nur Saqirah; Misran, Mohamad Harris; Meor Said, Maizatul Alice; Hassan, Nurmala Irdawaty (Asian Research Publishing Network (ARPN), 2023)
The purpose of this project was to develop a quad ridged horn antenna for a GSM and mid band 5G application, capable of dual frequency range operation at 1.8 GHz and 3.5 GHz. The antenna was constructed using 3D printing technology and Polylactic Acid (PLA), a thermoplastic polymer known for its high strength and compatibility with 3D printing processes. The impact of varying ridge width dimensions on the antenna's performance was evaluated using a range of parametric techniques. Ridge widths of 10 mm, 13.5 mm, and 17 mm were analysed to assess the effects of dimension alterations. Results demonstrated that the antenna is capable of dual band frequency operation with signal reflections of -16.89 dB and -28.60 dB at 1.8 GHz and 3.5 GHz, respectively. This research contributes to the development of efficient and cost-effective antennas for wireless communication applications in the GSM and mid band 5G spectrum.